Substance Use among a Sample of Healthcare Workers in Kenya: A Cross-Sectional Study. Issue 4 (7th August 2016) - Mokaya, Aggrey G.; Mutiso, Victoria; Musau, Abednego; Tele, Albert; Kombe, Yeri; Ng'ang'a, Zipporah; Frank, Erica; Ndetei, David M.; Clair, Veronic
ABSTRACT: This study describes reported substance use among Kenyan healthcare workers (HCWs), as it has implications for HCWs' health, productivity, and their ability and likelihood to intervene on substance use. The Alcohol Smoking and Substance Involvement Screening Test (ASSIST) was administered to a convenience sample of HCWs (n = 206) in 15 health facilities. Reported lifetime use was 35.8% for alcohol, 23.5% for tobacco, 9.3% for cannabis, 9.3% for sedatives, 8.8% for cocaine, 6.4% for amphetamine-like stimulants, 5.4% for hallucinogens, 3.4% for inhalants, and 3.9% for opioids. Tobacco and alcohol were also the two most commonly used substances in the previous three months. Male gender and other substance use were key predictors of both lifetime and previous three months' use rates. HCWs' substance use rates appear generally higher than those seen in the general population in Kenya, though lower than those reported among many HCWs globally. This pattern of use has implications for both HCWs and their clients.